Transportation and revolt : pigeons, mules, canals, and the vanishing geographies of subversive mobility - Shell, Jacob, 1983- (Cambridge, Massachusetts : MIT Press, 2015)
"Modes of transportation understood, by political regimes in different times and places, as intrinsically useful for clandestine movement, subversive mobility, and smuggling for revolt. Contents: Chapters look at canal transportation, several types of animal transportation (mules, elephants, camels and sled-dogs are all treated at some length), and inner-city freight-carrying infrastructure"--Provided by publisher.
Mules and upland banditry -- Transportation across intermediate states of matter -- Elephants, shat khats, and seas of mud -- Camels and granules -- The Asian elephant in Africa: paths not taken -- Many-headed monsters and guerrilla sled dogs -- Pidgin coalitions -- Unmappable mobility and the elements: six geographies of possibility -- Fly-boaters, filibusters, and canals -- Britain's missing ship canal era -- Railroads versus canals -- Canal people -- Ribbonists, Fenians, and waterways -- Dempingen -- Chenangoes: the replanning of freight flows in New York City -- Why doesn't New York City have a subway system for freight? -- The Chenangoes of throttled! -- Casual harbor work, shadow manufacturing, and comprehensive planning -- Transshipment of uranium -- Contrasting visions of transport labor.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Transportation and state -- History; Transportation -- Social aspects; Subversive activities -- Prevention; Insurgency; Smuggling -- Prevention; Pack animals (Transportation); Electronic books